Assessing the attitudes and knowledge of medical students towards Patient-Centred Care across different study years: a cross-sectional study - Muhammad Hamayal; Iqra Iftikhar; Muhammad Danyal Tahir; Muhammad Bilal Nadeem; Warda Shahid; Altaf Hussain (Journal of the Pakistan Medical Association)
Objective: To determine how medical students viewed the importance of patient-doctor communication, to assess their knowledge about patient-centred care, and to compare the attitudes of medical students in their pre-clinical and clinical years of study towards patient-centred care.